Cerebrospinal fluid biochemical studies in patients with Parkinson's disease: toward a potential search for biomarkers for this disease - Jiménez-Jiménez, Félix J.; Alonso-Navarro, Hortensia; García-Martín, Elena; Agúndez, José A. G. (Frontiers in Cellular Neuroscience, 2014)
The blood-brain barrier supplies brain tissues with nutrients and filters certain compounds from the brain back to the bloodstream. In several neurodegenerative diseases, including Parkinson’s disease (PD), there are disruptions of the blood-brain barrier. Cerebrospinal fluid (CSF) has been widely investigated in PD and in other parkinsonian syndromes with the aim of establishing useful biomarkers for an accurate differential diagnosis among these syndromes. This review article summarizes the studies reported on CSF levels of many potential biomarkers of PD. The most consistent findings are: (a) the possible role of CSF urate on the progression of the disease; (b) the possible relations of CSF total tau and phosphotau protein with the progression of PD and with the preservation of cognitive function in PD patients; (c) the possible value of CSF beta-amyloid 1-42 as a useful marker of further cognitive decline in PD patients, and (d) the potential usefulness of CSF neurofilament (NFL) protein levels in the differential diagnosis between PD and other parkinsonian syndromes. Future multicentric, longitudinal, prospective studies with long-term follow-up and neuropathological confirmation would be useful inestablishing appropriate biomarkers for PD.